An analysis of the physical contexts of crime in urban spaces and the provision of preventive design solutions, case study: Enghelab Street in Tehran - Fatemeh Saffarsabzevar (تحقیقات کاربردی علوم جغرافیایی)
One of the most effective approaches to enhancing urban security is crime prevention through environmental design (CPTED), which focuses on the role of urban design in reducing criminal behavior. This study aims to identify the specific environmental conditions that contribute to anomic and criminal behaviors on Enghelab Street in Tehran and to propose design solutions to mitigate these issues. The research employs a mixed-method approach to achieve its objectives. In the first phase, the Placecheck technique—which includes field surveys, expert checklists, and comprehensive checklists—was used to assess and categorize the environmental conditions of the study area. Based on this analysis, potential solutions to reduce crime were proposed. In the second phase, the Analytic Network Process (ANP) method was applied to prioritize these solutions and identify the most effective strategies for crime prevention and reduction in the area. The findings of this study reveal that environmental pollution, visual clutter, overcrowding, and inadequate nighttime lighting are the most significant environmental factors contributing to crime on Enghelab Street. The most effective solutions to reduce crime and enhance security in the area include: removing obstructive furniture and elements from pedestrian pathways, clearly defining activities and land uses in ambiguous spaces, installing signage and landmark elements along the route, regulating advertisements, and implementing standardized nighttime lighting to support safe activities. The results of this research demonstrate that even minor environmental modifications can have a substantial impact on reducing crime and improving security.